Collaborative knowledge and new rurality - Sanz-Martos, Sandra (Anuario ThinkEPI, 2022)
New rurality was created with the aim of creating opportunities through connectivity, mobility, and the personal and professional advancement of women. Given this context, initiatives to provide collaborative solutions are becoming increasingly common and make greater use of dynamics that facilitate the exchange of knowledge, information, and experiences. Associations, the social economy, food cooperatives, cohousing, inclusive projects, and hackathons help create rural communities that are more capable, entrepreneurial, cohesive, and collaborative.